2020
DOI: 10.3390/en13195201
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Methods for Investigation of Drilling Fluid Displacement in Irregular Annuli

Abstract: Experimental methods are still indispensable for fluid mechanics research, despite advancements in the modelling and computer simulation field. Experimental data are vital for validating simulations of complex flow systems. However, measuring the flow in industrially relevant systems can be difficult for several reasons. Here we address flow measurement challenges related to cementing of oil wells, where main experimental issues are related to opacity of the fluids and the sheer size of the system. The main ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…7 in concentric geometries with the same used fluids, densities, and rheologies, it can be seen that the higher flow rate of 21.6 L/min in the eccentric geometry than 7.86 L/min in the concentric geometry causes lower effective viscosity, and the recorded pressure gradients in the eccentric geometry are higher than the concentric geometry. While it is known that frictional pressure drop in an eccentric annulus is lower than in a corresponding concentric annulus [24], due to the dominating hydrostatic pressure gradient and somewhat different fluid and flow properties from test to test, this is not apparent from our experiments here. The observed differences of pressure gradients in the eccentric and concentric Hele-Shaw cells are due to the flow rate differences and consequently equivalent viscosity differences rather than the degree of eccentricity.…”
Section: Pressure Gradient Analysismentioning
confidence: 55%
See 1 more Smart Citation
“…7 in concentric geometries with the same used fluids, densities, and rheologies, it can be seen that the higher flow rate of 21.6 L/min in the eccentric geometry than 7.86 L/min in the concentric geometry causes lower effective viscosity, and the recorded pressure gradients in the eccentric geometry are higher than the concentric geometry. While it is known that frictional pressure drop in an eccentric annulus is lower than in a corresponding concentric annulus [24], due to the dominating hydrostatic pressure gradient and somewhat different fluid and flow properties from test to test, this is not apparent from our experiments here. The observed differences of pressure gradients in the eccentric and concentric Hele-Shaw cells are due to the flow rate differences and consequently equivalent viscosity differences rather than the degree of eccentricity.…”
Section: Pressure Gradient Analysismentioning
confidence: 55%
“…The frictional pressure drop and the relation between pressure drop and flow rate during the displacement flow of non-Newtonian fluids were described as well [4,10,11]. By using large-scale eccentric annular geometry, the importance of the rheological properties of the realistic non-Newtonian fluids for fluid flow and hole cleaning performance was expressed extensively [14][15][16], and the propagation of the fluid interfaces and displacement efficiency were characterized [24]. It was indicated that an enlarged irregular section, i.e., a washout causes an improvement in displacement in some scenarios in strongly inclined wellbores [17]; while being independent of the displacement efficiency in the washout itself, the presence of washouts may lead to poorer cement quality downstream of the washouts [23].…”
Section: Introductionmentioning
confidence: 99%